2022
DOI: 10.21608/msadj.2022.268236
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Marginal Adaptation of Two CAD/CAM Glass Ceramic Occlusal Veneers at Different thickness After Thermodynamic aging

Abstract: Background: Occlusal veneers fabricated with different materials and thicknesses can reveal different marginal adaptation after thermodynamic aging.Methodology: Extracted maxillary premolar teeth (n=28) were collected and embedded in epoxy resin block with light body material then randomized according to materials into two groups (n=14): Lithium disilicate IPS e.max CAD (A) and Zirconia reinforced lithium silicate Celtra Duo (B) then further randomized into four subgroups (n=7) according to occlusal veneer thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…(67) Group CD table-tops fabricated from Celtra DUO, showed better marginal and internal adaptation than table-tops fabricated from e.max CAD in group ED. This result came in agreement with Ahmed et al, (74) Basheer et al, (75) , and Abuhajar et al, (42) , the microstructure of Celtra Duo, as manufacturer claims, presented increased edge stability, so offering satisfactory margins. (76) While inferior marginal and internal adaptation of e. max CAD resulted from dimension changes that happened during the crystallization firing stage as CD restorations were milled in a fully crystallized state, while ED restorations were milled in partially crystallized form.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…(67) Group CD table-tops fabricated from Celtra DUO, showed better marginal and internal adaptation than table-tops fabricated from e.max CAD in group ED. This result came in agreement with Ahmed et al, (74) Basheer et al, (75) , and Abuhajar et al, (42) , the microstructure of Celtra Duo, as manufacturer claims, presented increased edge stability, so offering satisfactory margins. (76) While inferior marginal and internal adaptation of e. max CAD resulted from dimension changes that happened during the crystallization firing stage as CD restorations were milled in a fully crystallized state, while ED restorations were milled in partially crystallized form.…”
Section: Discussionsupporting
confidence: 90%
“…(39) In addition, keeping a minimal cement thickness enhances the accurate insertion of the table-tops and allows insertion of an even thickness of cement layer with average values ranged from 25 to 50µm at the margin. (40) Table-tops of 1 mm thickness were applied in the present study simulating many published literature, (41,42) As a systematic review by Albelasy et al who concluded that lithium disilicate glass ceramic showed a satisfactory fracture strength results of the table-tops fabricated at a thickness of 0.7-1.0 mm. (43) Marginal adaptation is crucial as cement exposure to the oral environment leads to subsequent cement dissolution and development of secondary caries.…”
Section: Discussionmentioning
confidence: 94%
“…The most important technical factor for long-term restoration success and enhanced prosthesis retention is marginal adaptation of fixed prosthodontics (31) . Marginally, the tissues surrounding restorations and their long-term durability are affected by design of the finish line and materials used (34) .…”
Section: Discussionmentioning
confidence: 99%
“…Each etched surface was rinsed with water spray for 60 seconds and then air dried for 20 seconds. A layer of silane coupling agent (Bisco, Company, USA) was applied for 60 seconds to the etched surface, and then air thinned (31) . Each tooth was etched using 37% phosphoric acid (Meta Biomed, Korea) and then a universal bond (Bisco, Company, USA) was applied.…”
Section: Cementationmentioning
confidence: 99%
See 1 more Smart Citation